A community-based tourism strategy: Homestays towards sustainable development - Sahadev Gautam (Journal of Rural Tourism, 2025)
Purpose – This study explores sustainable resource management through community-based tourism, focusing on Panauti Community Homestay as a model for integrating hospitality, cultural preservation, and local participation. Methodology – A qualitative approach was applied using ethnographic observations and checklist-based interviews, supported by both primary and secondary data.Findings – Homestays offer authentic experiences for travelers while enhancing community well-being. Collective decision-making and local engagement play key roles in sustaining tourism and preserving cultural and ecological values.Originality – This research presents community homestays as grassroots models for sustainable tourism, highlighting their potential to empower local communities and promote responsible travel practices.